EUROCARE-4. Survival of cancer patients diagnosed in 1995-1999. Results and commentary. - Sant, Milena; Allemani, Claudia; Santaquilani, Mariano; Knijn, Arnold; Marchesi, Francesca; Capocaccia, Riccardo; Renseigné, Non; Danzon, Arlette (European Journal of Cancer, 2009)
International audience EUROCARE-4 analysed about three million adult cancer cases from 82 cancer registries in 23 European countries, diagnosed in 1995-1999 and followed to December 2003. For each cancer site, the mean European area-weighted observed and relative survival at 1-, 3-, and 5-years by age and sex are presented. Country-specific 1- and 5-year relative survival is also shown, together with 5-year relative survival conditional to surviving 1-year. Within-country variation in survival is analysed for selected cancers. Survival for most solid cancers, whose prognosis depends largely on stage at diagnosis (breast, colorectum, stomach, skin melanoma), was highest in Finland, Sweden, Norway and Iceland, lower in the UK and Denmark, and lowest in the Czech Republic, Poland and Slovenia. France, Switzerland and Italy generally had high survival, slightly below that in the northern countries. There were between-region differences in the survival for haematologic malignancies, possibly due to differences in the availability of effective treatments. Survival of elderly patients was low probably due to advanced stage at diagnosis, comorbidities, difficult access or lack of availability of appropriate care. For all cancers, 5-year survival conditional to surviving 1-year was higher and varied less with region, than the overall relative survival.